Postponing sleep after a stressful day: patterns of stress, bedtime procrastination, and sleep outcomes in a daily diary approach - Schmidt, Laura; Baetzner, Anke; Dreisbusch, Marina Isabella; Mertens, Alica; Sieverding, Monika (Stress and health, 2024)
Sleep problems and stress are common among students and are associated with negative effects on academic performance as well as mental and physical health risks, but studies exploring mediating factors between stress and sleep on a daily basis are scarce. This study aimed to investigate the relationship of daily stress, Bedtime procrastination (BP) (i.e., postponing bedtime without external reasons), and sleep outcomes controlling for trait factors such as self-control. N = 96 students at a German university (M = 22.2 years, SD = 4.0) wore a sleep-tracking wearable (Fitbit Charge HR) for two weeks to assess sleep duration and to calculate the gap between the intended time to go to sleep and the objectively measured time of falling asleep. Stress, intended time to go to sleep, and sleep quality were assessed via daily diaries. Established questionnaires were used to measure trait self-control, trait BP, and smartphone addiction. Multilevel analyses indicated that more stress experienced during the day was associated with more BP (b = 2.32, p = 0.008), shorter sleep duration (b = −3.46, p = 0.003), and lower sleep quality (b = 1.03, p = 0.005) after controlling for several trait factors. The association of daily stress with sleep outcomes (quality and duration) was partly mediated by BP. Our findings indicate that BP might be one factor that contributes to stress-linked decreases in sleep duration and quality. Potential reasons for stress-related later time to fall asleep—like higher physiological arousal or stress-related worries—should be investigated in future studies.